5β-reduced neuroactive steroids as modulators of growth and viability of postnatal neurons and glia - Munawar Cheema, Marie; Macakova Kotrbova, Zuzana; Hrcka Krausova, Barbora; Adla, Santosh Kumar; Slavikova, Barbora; Chodounska, Hana; Kratochvil, Miroslav; Vondrasek, Jiri; Sedlak, David; Balastik, Martin; Kudova, Eva (Journal of steroid biochemistry and molecular biology, 2024)
Endogenous neurosteroids (NS) and their synthetic analogs, neuroactive steroids (NAS), are potentially useful drug-like compounds affecting the pathophysiology of miscellaneous central nervous system disorders (e.g. Alzheimer ́s disease, epilepsy, depression, etc.). Additionally, NS have been shown to promote neuron viability and neurite outgrowth upon injury. The molecular, structural and physicochemical basis of the NS effect on neurons is so far not fully understood, and the development of new, biologically relevant assays is essential for their comparative analysis and for assessment of their mechanism of action. Here, we report the development of a novel, plate-based, high-content in vitro assay for screening of NS and newly synthesized, 5β-reduced NAS for the promotion of postnatal neuron survival and neurite growth using fluorescent, postnatal mixed cortical neuron cultures isolated from thy1-YFP transgenic mice. The screen allows a detailed time course analysis of different parameters, such as the number of neurons or neurite lengths of 7-day, in vitro neuron cultures. Using the screen, we identify a new NAS, compound 42, that promotes the survival and growth of postnatal neurons significantly better than several endogenous NS (dehydroepiandrosterone, progesterone, and allopregnanolone). Interestingly, we demonstrate that compound 42 also promotes the proliferation of glia (in particular oligodendrocytes) and that the glial function is critical for its neuron growth support. Computational analysis of the biological data and calculated physicochemical properties of tested NS and NAS demonstrated that their biological activity is proportional to their lipophilicity. Together, the screen proves useful for the selection of neuron-active NAS and the comparative evaluation of their biologically relevant structural and physicochemical features.
Keywords: Neurites; myši transgenní; oligodendroglie; Mice; Animals; Neurosteroids; Mice, Transgenic; Neurons; myši; Progesterone; Oligodendroglia; zvířata; neurosteroidy; neurony; progesteron; neurity